Manipulation of Supramolecular Columnar Structures of H‐Bonded Donor‐Acceptor Units through Geometrical Nanoconfinement. Issue 6 (27th February 2019) - Park, Wongi; Feringán, Beatriz; Yang, Minyong; Ryu, Seong Ho; Ahn, Hyungju; Shin, Tae Joo; Sierra, Teresa; Giménez, Raquel; Yoon, Dong Ki
Abstract: Ambipolar organic semiconductors are considered promising for organic electronics because of their interesting electric properties. Many hurdles remain yet to be overcome before they can be used for practical applications, especially because their orientation is hard to control. We demonstrate a method to control the orientation of columnar structures based on a hydrogen (H)‐bonded donor‐acceptor complex between a star‐shaped tris(triazolyl)triazine and triphenylene‐containing benzoic acid, using physicochemical nanoconfinement. The molecular configuration and supramolecular columnar assemblies in a one‐dimensional porous anodic aluminium oxide (AAO) film were dramatically modulated by controlling the pore‐size and by chemical modification of the inner surface of the porous AAO film. In situ experiments using grazing‐incidence X‐ray diffraction (GIXRD) were carried out to investigate the structural evolution produced at the nanometer scale by varying physicochemical conditions. The resulting highly ordered nanostructures may open a new pathway to effectively control the alignment of liquid crystal ambipolar semiconductors. Abstract : Geometrical nanoconfinement : We successfully controlled the orientation of the supramolecular structure made from a donor‐acceptor complex, and their detailed features are visualized. Depending on the substrate's physical size and chemical condition, the donor‐acceptor complexes formed different superstructures with different orientations. Based on this structural control and analysis, p–n junction based organic electronics can be realized in the near future.